2012
DOI: 10.1121/1.3672701
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of quantitative ultrasound parameters with cancellous bone microstructure in human calcaneus in vitro

Abstract: Ultrasound parameters (attenuation, phase velocity, and backscatter), bone mineral density (BMD), and microarchitectural features were measured on 29 human cancellous calcaneus samples in vitro. Regression analysis was performed to predict ultrasound parameters from BMD and microarchitectural features. The best univariate predictors of the ultrasound parameters were the indexes of bone quantity: BMD and bone volume fraction (BV/TV). The most predictive univariate models for attenuation, phase velocity, and bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 89 publications
(111 reference statements)
3
36
1
Order By: Relevance
“…18 Wear et al also found that the nBUA was highly correlated to the porosity (r ¼ À0.85) but not significantly to the trabecular spacing (r ¼ À0.22) in 29 human calcaneal trabecular bone samples. 16 As found in Figs. 3(a) and 3(b), the dependence of the SOS on the porosity and the trabecular spacing exhibited a behavior opposite to that of the nBUA.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…18 Wear et al also found that the nBUA was highly correlated to the porosity (r ¼ À0.85) but not significantly to the trabecular spacing (r ¼ À0.22) in 29 human calcaneal trabecular bone samples. 16 As found in Figs. 3(a) and 3(b), the dependence of the SOS on the porosity and the trabecular spacing exhibited a behavior opposite to that of the nBUA.…”
Section: Resultssupporting
confidence: 71%
“…15 Wear et al also observed that the SOS was negatively correlated with the porosity (r ¼ À0.77) and the trabecular spacing (r ¼ À0.25) in 29 human calcaneal trabecular bone samples. 16 As predicted by using Biot's theory for elastic wave propagation in fluid-saturated porous media, the slow wave velocity in trabecular bone increases with increasing porosity, and the fast wave exhibits an opposite dependence on the porosity. 17 Hence, the positive correlations of the SOS with the porosity and the trabecular spacing obtained in the present study underpins the fact that the signals transmitted through the phantoms consisting of water-saturated aluminum foams correspond to the slow wave.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…5 The relationships of SOS and nBUA with BMD and microarchitectural parameters not only in human calcaneus but also in femur in vitro have been extensively reported by a number of authors. [6][7][8][9][10][11] In contrast, few authors investigated nonlinear ultrasonic behaviors of bone. [12][13][14][15][16][17][18] The nonlinear elastic parameter B/A is defined as the first-order pressure derivative of the elastic modulus (the bulk modulus for a fluid).…”
Section: Introductionmentioning
confidence: 99%